The Role of Technology in Promoting Assessment Literacy in ELT - Ledy Nurlely (Journal of Linguistics, Literacy, and Pedagogy, 2023)
This article examines the role of technology in promoting assessment literacy in English Language Teaching (ELT). Assessment literacy is defined as teachers' understanding and competency in assessment practices and principles, which includes knowledge of assessment design, implementation, evaluation, and interpretation. The article highlights the importance of assessment literacy in ELT, as it enables teachers to make informed decisions about assessment methods, evaluate and interpret assessment results, and provide meaningful feedback to learners. Technology-assisted assessment is explored, highlighting the benefits and challenges of using technology to enhance assessment literacy in ELT. The article discusses how technology can provide teachers with access to assessment resources and materials, develop assessment skills and knowledge, and facilitate real-time feedback and assessment. Best practices for integrating technology in assessment literacy are presented, and examples of technology-assisted assessment in ELT are provided. The article concludes that technology has the potential to transform assessment practices in ELT, and enhance assessment literacy among teachers. It emphasizes the importance of assessment literacy in supporting students' language learning needs and the potential of technology to promote assessment literacy. The article recommends that ELT teachers should develop their assessment literacy and consider incorporating technology-assisted assessment methods into their teaching practices.